Van der woude syndrome- a case report - Hasan, Shamimul; Khan, Nabeel Ishrat (Recent Research in Science and Technology, 2012)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Van der Woude syndrome (VWS) is a rare, autosomal dominant disorder, caused by deletions in the chromosome band 1q32-q41, and characterized by cleft lip or cleft palate, distinctive pits of the lower lips, or both. The most prominent and consistent features of Van der Woude syndrome are oro-facial defects. The oro-facial abnormalities include lower lip pits alone, hypodontia, or isolated cleft lip and cleft palate of varying severity. A case of Van der Woude syndrome, with the typical manifestations in a seven year old male patient is being presented, along with its review of literature.